Does the MAX effect exist in the Philippine stock market? - Ko, Kino Denzel (Animo Repository, 2023)
This study explores the MAX effect in the Philippine Stock Market and found strong evidence for the existence of the MAX effect in the Philippine Stock Market, as demonstrated by the consistent underperformance of high-MAX stocks relative to low-MAX stocks. This finding persists even after controlling for various market factors. The existence of the MAX effect in the stock market of a developing country is interesting to note as this implies that the phenomenon is not limited to developed markets, as situated in most studies on the MAX effect. Furthermore, this suggests that heuristic biases and gambling behavior among investors may be prevalent across various regions, regardless of their level of development. Moreover, this highlights the importance of conducting research in different markets to gain a more comprehensive understanding of market anomalies and investor behavior. Overall, these results contribute to our understanding of stock performance in the Philippine Stock Market and have implications for investor decision-making and portfolio management.